OLOS Swiss - Burgi, Pierre-Yves; Cazeaux, Hugues; Jelicic, André (Revue électronique suisse de science de l'information (RESSI), 2022)
During the P-5 program (2019-2020), the DLCM1 services transitioned from pilot to operational status: a data management training program and ad-hoc support were delivered throughout Switzerland, and OLOS (olos.swiss), the long-term solution for research data archiving and publication, became operational. Yareta, powered by the same DLCM technology than OLOS, was launched in June 2019, serving all the Higher Education Institutions of the Geneva Canton. Thanks to OLOS, the next step is to launch in January 2021 an equivalent service at the National level.